PENGELOLAAN PENDIDIKAN KARAKTER TERHADAP REMAJA MELALUI PENDEKATAN NILAI-NILAI KEISLAMAN - Aspandi, Ade (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2020)
In general, this research intends to reduce the number of youth delinquency through the management of character education by Islamic values engraft. It is done by involving the youth in some Islamic activities as an effort to create the youth own character to be better. This research uses a qualitative approach, which also uses a case study method. This research describes the role of Karang Taruna Widarasari Village to manage the youth character education through the Islamic values ​​in routines Islamic form, and it is done by examining Ki Hajar Dewantara’s Thought who is the author of education. Based on the results of this research which has done, the management of character education for youth through of Islamic values engraft ​​by Karang Taruna Widarasari Village is done through some Islamic activities such as, the evening prayer recitation (daily routine), Islamic speech and training the traditional Islamic art (weekly routine). To create the youth character, the Islamic activities are committed to invent the youth habitual by following the Islamic activities.